DETERMINANTES SOCIOECONOMICOS DEL TABAQUISMO EN EL ECUADOR” - González Cango, Christian Daniel (2019)
The present investigation analyzes the main factors that influence smoking, especially the role of schooling and income in Ecuador. We use data from the National Survey of Nutrition and Health of the year 2012 of the National Institute of Statistics and Census, and discrete choice models to capture the incidence of some personal and cultural features, characteristic of Ecuador. The dependent variable is whether you smoke in the last 30 days or not; while the independent variables are years of schooling and level of income. Added control variables that are age, gender, ethnicity, area, occupation category, social security and natural region in which the individual lives. The results obtained are classified into two groups: in the first, they show that there is a statistical significance for the variables schooling and income, then in the second group when control variables are added the income continues to be significant but schooling is not, likewise, there is a statistical significance for the variables gender, indigenous ethnic group, social security and natural region. With these results it was concluded that the individuals most likely to smoke are those with less education than men, who do not have social security and who reside in the Sierra and Amazon region. Among the policy implications based on this study for Ecuador, it is recommended to orient public programs such as support groups that try to reduce smoking figures, to the segments of the population described as more prone to smoking in this research. In addition, use as a tool, education, which as demonstrated can reduce the likelihood of smoking in people and even more if it is directed to that goal.